An introduction to the early development of mathematics - Goodman, Michael K. J. (John Wiley & Sons, Inc., 2016)
An easy-to-read presentation of the early history of mathematics Engaging and accessible, An Introduction to the Early Development of Mathematics provides a captivating introduction to the history of ancient mathematics in early civilizations for a nontechnical audience.